B-lymphocytes forming follicle-like structures in the lung tissue of tuberculosis-infected mice: Dynamics, phenotypes and functional activity. (January 2017) - Linge, Irina; Dyatlov, Alexander; Kondratieva, Elena; Avdienko, Vadim; Apt, Alexander; Kondratieva, Tatiana
Abstract: During tuberculosis (TB) infection, B cells form follicles in close vicinity of lung granuloma. We assessed the dynamics of follicle formation, surface phenotypes and functional activity of lung B cells during TB course in genetically susceptible mice. The follicles appeared early post infection and peaked at weeks 7–8. Lung B cells resembled classical B2 cells (CD19 + IgMloIgD hi CD1d − CD21/35 int CD5 − CD11b − CD43 − ), but differed from them by the absence of B2 marker CD23. Lung B-cells constitutively expressed MHC II molecules, presented mycobacterial antigens to immune CD4 + T-cells and produced high amounts of IL-6 and IL-11, but no classical type 1 (TNF-α, IFN-γ), or anti-inflammatory (IL-10, TGF-β) cytokines. The total antibody response in tuberculous lung showed almost no specificity to mycobacteria. A panel of monoclonal antibodies obtained from lung B cells contained only few clones with reactivity to mycobacteria. Our results suggest that anti-TB B cell response in the lung has clear pathological and doubtful protective role.